Personal Brand Creation in the Digital Age Theory, Research and Practice - Grzesiak, Mateusz (Springer International Publishing, 2018)
Presenting a scientific exploration of personal branding and digital communication, this ground-breaking book aims to fill a gap between theory and practice. Describing how social media can increase brand profiles online, it explains basic terms before investigating the cultural context for online personal branding. With a special focus on YouTube, the author provides a comparative analysis of two countries (USA and Poland) to open further avenues for research into this growing area. An essential read for management and marketing scholars, this study outlines and explores the evolution of media in the digital age from a business perspective, and offers a thought-provoking analysis for those interested in social media.